Comparative study among aqueous, hexane extracts of sweet almond (Prunusamygdalus) with Atorvastatin for treating hyperlipidemia induced in mice - Kafi, Lubna A.; Al- Ezzi, Noor TH. N. (Kufa Journal For Veterinary Medical Sciences, 2015)
This research was developed to find out the treatment impact of aqueous and hexane extracts of sweet almond (Prunusamygdalus) on some biological indicators related to hyperlipidemia that induced inmiceand comparative with Atorvastatin which was dried and grinded by an electrical grinder to form fine crude powderthat extracted by two ways:by using 95% hexaneandwaterby using thedistilledwater with Soxhlet apparatus, (40) of mature mice were randomly separated into 8 categories (5 mouse per group) and treated every day for 60 days, the first group was fed and drank normally and regarded as a negative control group (NC1), a second group was given polypropylene glycol offered as negative control group (NC2), third group was given normal water containing 0.5% of hydrogen peroxide and 1% of cholesterol in the feed for 60 days for induction of hyperlipidemia and offered as positive control group (PC), hyperlipidemia was induced in the other five categories as in the third group.Treated hyperlipidemia by hexane extract at a dose of 500 mg/ kg of body weight and aqueous extract of sweet almond with three different doses (500, 750 and 1000) mg/ kg of bodyweight and compared with the other groups that treated with atorvastatin (Lipitor) ® 20 mg/ kg B.W. as antihyperlipidemic drug. The outcomes discovered that oral dosing with extracts of sweet almond and medication therapy led to acquire beneficial changes in the parameters, which were showed incident of a significant decrease (P<0.05) at a concentration of malondialdehyde (MDA), total cholesterol (TC), triacylglycerol (TAG), low density lipoprotein cholesterol (LDL-C), very low density lipoprotein cholesterol (VLDL-C) and atherogenic index (AI) in serum, moreover to a significant improved (P<0.05) in the concentration of high density lipoprotein cholesterol (HDL-C) and serum reduced glutathione (GSH) comparedwithuntreated group and has been proven that a dose of 1000 mg/kg of aqueous extracts of sweet almond was the best in therapy.